A perspective on integrated dialysis access management: in advance of integrated care plan - Beatriz Gil Braga; Joana Tavares; Maria João Carvalho (RDPLF, 2024)
(To read the full article, in English or French, click on the pdf logo on the right). We would like to draw attention to the critical issue of dialysis access management and vascular access (VA) options in patients transitioning to chronic renal replacement therapy and from peritoneal dialysis (PD) to hemodialysis (HD). We advocate for the establishment of dedicated consultation services for integrated dialysis access management to optimize patient outcomes. We highlight specific cases where a tailored approach to VA selection is essential, emphasizing the importance of risk stratification and timely access preparation. The preferred use of arteriovenous fistula in HD patients and the challenges surrounding its maturation are discussed. We also explore circumstances necessitating urgent versus planned transitions to HD, incorporating considerations for patient-centered care and education. Sonography's role in managing PD-related infections and the potential benefits of home HD in the transition process are also examined. We suggest the development of scoring systems to predict patient transitions and emphasize the need for an integrated approach to dialysis access management. Overall, we advocate for proactive measures to prevent vascular access failure and ensure a safe and effective transition process for patients with chronic kidney disease.